I am in transitional math and I am doing an algebra problem and I am not sure I know how to solve it. 4y-2(y-2)+3
Thank you for the opportunity to help you with your question!
ok i will help you just should you write the eqution on the right form ok :
if the equation is :
4y-2(y-2)+3 = 0
4y - 2y + 4 + 3 = 0
2y + 7 = 0
2y = -7
y = -7/2
if you don't understand please just ask
i am glad to work with you just invite me
The correct answer according to the mymathlab is 2y+7 not 2y-7
ahh so is not an equation is factoring
so the answer is :
4y-2(y-2)+3 = 4y - 2y + 4 + 3 = 2y + 7
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?